2008
DOI: 10.1021/bi801580e
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Water Reactions during the S-State Cycle of the Photosynthetic Water-Oxidizing Center: Detection of the DOD Bending Vibrations by Means of Fourier Transform Infrared Spectroscopy

Abstract: Photosynthetic water oxidation takes place in the water-oxidizing center (WOC) of photosystem II (PSII). To clarify the mechanism of water oxidation, detecting water molecules in the WOC and monitoring their reactions at the molecular level are essential. In this study, we have for the first time detected the DOD bending vibrations of functional D 2O molecules during the S-state cycle of the WOC by means of Fourier transform infrared (FTIR) difference spectroscopy. Flash-induced FTIR difference spectra upon S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
120
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(140 citation statements)
references
References 44 publications
(114 reference statements)
19
120
1
Order By: Relevance
“…Mn III/IV , purple; Ca 2+ , yellow; oxo-bridges, red; water–oxygens, blue; Cl − , green; amino acid backbones, grey; carboxy-oxygen, red; and His-nitrogen, dark blue. ( b ) Kok cycle for water oxidation in PSII including proton release to the bulk822 (see also Supplementary Note 1) and water-binding events2728. The S i states ( i =0, …, 4) denote the oxidation state of the Mn 4 CaO 5 cluster relative to the S 0 state, while the plus sign indicates a positive extra charge.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Mn III/IV , purple; Ca 2+ , yellow; oxo-bridges, red; water–oxygens, blue; Cl − , green; amino acid backbones, grey; carboxy-oxygen, red; and His-nitrogen, dark blue. ( b ) Kok cycle for water oxidation in PSII including proton release to the bulk822 (see also Supplementary Note 1) and water-binding events2728. The S i states ( i =0, …, 4) denote the oxidation state of the Mn 4 CaO 5 cluster relative to the S 0 state, while the plus sign indicates a positive extra charge.…”
Section: Figurementioning
confidence: 99%
“…It is widely agreed that this dioxygen-forming reaction sequence starts with a proton release during the transition22232425, followed by the formation of a Ca- or Mn-bound oxyl radical or of a Mn V -oxo group due to oxidation of the cluster by 61426. Although the following reaction steps towards O 2 must include the formation of a bound peroxidic intermediate, dioxygen formation and release, and the rebinding of substrate water2728 (Fig. 1c), the exact nature of the chemistry involved remains unsettled, as these transient states have so far largely eluded biophysical investigations6142829303132.…”
mentioning
confidence: 99%
“…On the other hand, for the S1 → S2 transition, the OEC core geometry was almost unchanged, and no proton release was observed. Thus, the S1 → S2 transition is expected to be a simple one-electron oxidation reaction [4,8]. Therefore, the first chemical reaction of PSII-OEC is considered to occur during the S2 → S3 transition.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Changes in the D-O-D bending of water molecules have been detected, as well. 35 It was shown that the exchange of the protein solvent from H 2 16 O to H 2 18 O is enough to detect dangling waters in the dark state of BR, without the need to induce a photoreaction. 36 In the present work, another class of the large family of retinylidene proteins was studied.…”
mentioning
confidence: 99%